Services in the international market - Jelisavac Sanja (Međunarodni Problemi, 2008)
The author analyses the role of services in the international market. Services sector has significant influence on economic growth and efficiency. Share of services in the world market is in the contrast with great role they play in the domestic market. Because of their intangible nature the trade in services is subject to a much large limitations than the trade in goods. Insufficient data or incomparable data on international trade in services makes this sector hard to analyze. Brought together to solve those problems few international organizations have made Manual on Statistics of International Trade in Services. This and many others are ongoing work to set internationally comparable data for the future analysis.